Development of a method for the analysis of serglycin proteoglycan gene expression in canine blood samples - Löfqvist, Kristin (2018)
Cancer is a highly prevalent disease among canine breeds. Nowadays, mainly histology parameters are used to determine the prognosis and for selecting treatment strategies. Due to the high degree of morbidity and mortality in cancer affected dogs, there is a strong need to identify additional diagnostic methods and biomarkers. Serglycin is an intracellular proteoglycan found to be overexpressed in several types of cancer, including aggressive canine mammary cancer. High expression levels of serglycin in cancer cells are con- sidered to correlate with cancer metastases and a poor prognosis for the patient. Detection of serglycin expression may, therefore, be a potential diagnostic marker for metastatic cancer in canine breeds. A known molecular technology used daily in medical diagnostics is quantitative polymerase chain reaction (qPCR). QPCR is primarily used to identify the expression pattern of specific genes. The aim of this study was to establish a qPCR assay that could be used for de- tection of serglycin expression in canine blood. The focus of the study was to validate potential reference genes as well as optimiza- tion of a functional qPCR assay. For this purpose, blood samples from canine donors with unknown disease history were chosen. Total RNA from each blood sample was extracted it an optimized TRIzol protocol. The samples were first tested in a step-down PCR, and then further tested in three different qPCR optimization steps. Both the step-down PCR and the qPCR included four genes;; SRGN and three references genes EEF2, HPRT and ACTIN B. The qPCR assays showed high specificity and sensitivity for two of the genes, SRGN and EEF2.Primer pairs for each of the two genes showed efficiency values within the range of 90 % to 105%, and their reflec- tion of linearity was R2>0.980. The optimal annealing temperature for the SRGN and EEF2 gene was set as 62 °C with a 300 nM primer concentration. Unfortunately, the published primer-design for two of the reference genes, i.e. HPRT and ACTIN B were poorly designed resulted in amplification of unwanted DNA and primer dimer for- mation. In conclusion, the presented method in this study showed evidence that serglycin could be detected in small amounts of canine blood utilizing the described qPCR assay. We concluded that the EEF2 gene is a stable reference gene for studying gene expression in dog blood with qPCR. However, in order to be able to apply our method in further studies, additional suitable reference genes need to be identified, tested and further validated.